Strategi Pengendalian Pencemaran Sungai Kampar Dengan Metode Analytical Hierarchy Process (AHP) (Studi Kasus : DAS Kampar Segmen Propinsi Sumatera Barat) - Tabrani Tabrani; Siswanto Siswanto; Iman Suprayogi (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2017)
Kampar River is the Main River, especially in Riau Province, which serves as a water drainage conditions can not be separated from human activities in the watershed. Conditions Kampar River is currently estimated to have experienced a decline in water quality due to various human activities that are in the catchment area. This study aims to formulate a strategic priority of the Kampar river water pollution control, the study area is located in the Upper River Region Kampar ie Pasaman of West Sumatra province and Regency Limapuluhkota. Water quality analysis conducted by the Centers for Disease Control and management of Sumatra Ecoregion (P3ES), using the parameter Biologycal Oxigen Demand (BOD), Chemical Oxigen Demand (COD), Total Suspended Solid (TSS). The result is has been a decline Kampar River water quality from upstream to downstream marked with the pollution index value tends to increase by Parameter Biologycal Oxigen Demand (BOD), Chemical Oxigen Demand (COD), Total Suspended Solid (TSS). To maintain the quality of water in their natural condition required river water pollution control strategy that is focused on (a) increasing the role of society, both the general public, farmers and the industry in efforts to control water pollution. (B) improving coordination among agencies related to water pollution control, and (c) integrated water pollution control policies in layout. Keywords: AHP, parameter pollution, pollution control, water quality status